2019
DOI: 10.1002/joc.6349
|View full text |Cite
|
Sign up to set email alerts
|

Climate signals in carbon and oxygen isotope ratios ofPinus cembratree‐ring cellulose from the Călimani Mountains, Romania

Abstract: We analyse annually resolved tree‐ring stable carbon (δ13C) and oxygen (δ18O) isotopic chronologies from Swiss stone pine (Pinus cembra L.) in Romania. The chronologies cover the period between 1876 and 2012 and integrate data from four individual trees from the Calimani Mts in the eastern Carpathians where climatic records are scarce and starts only from 1961. Calibration trials show that the δ13C values correlate with local April–May relative humidity and with regional to larger scale (European) summer preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 88 publications
(153 reference statements)
1
31
0
1
Order By: Relevance
“…The presented δ 13 C chronology is, to the best of our knowledge, the first stable carbon isotope chronology for endemic Balkan pines (P. heldreichii and P. peuce). Our composite P. heldreichii and P. peuce stable carbon isotope chronology has a similar climate signal in δ 13 C in tree-rings as δ 13 C chronologies from the Carpathians [21], Corsica [22,23], or the south-eastern Alps [24]. Even though our composite δ 13 C chronology correlates best with cloudiness, we decided to test a potential climate reconstruction model of summer temperatures, since the cloudiness dataset is short, with some missing data.…”
Section: Climate Signal In Stable Carbon Isotopes In Tree Ringsmentioning
confidence: 95%
See 1 more Smart Citation
“…The presented δ 13 C chronology is, to the best of our knowledge, the first stable carbon isotope chronology for endemic Balkan pines (P. heldreichii and P. peuce). Our composite P. heldreichii and P. peuce stable carbon isotope chronology has a similar climate signal in δ 13 C in tree-rings as δ 13 C chronologies from the Carpathians [21], Corsica [22,23], or the south-eastern Alps [24]. Even though our composite δ 13 C chronology correlates best with cloudiness, we decided to test a potential climate reconstruction model of summer temperatures, since the cloudiness dataset is short, with some missing data.…”
Section: Climate Signal In Stable Carbon Isotopes In Tree Ringsmentioning
confidence: 95%
“…However, there are δ 13 C chronologies for other tree species in the wider region, although the number of δ 13 C chronologies is smaller than in Western Europe, Fennoscandia, or parts of the Mediterranean region. Nagavciuc et al [21] developed a stable carbon and oxygen isotope chronology for Pinus cembra for the eastern Carpathian timberline and found that δ 13 C was negatively correlated with summer precipitation and three-month SPEI (Standardized Precipitation-Evapotranspiration Index) index. Szymczak et al [22,23] developed a 560-year summer temperature reconstruction for Corsica (France) based on a stable carbon isotope from Pinus nigra tree-rings.…”
Section: Introductionmentioning
confidence: 99%
“…Holocene wood sections were available at the Department of Geography of the University of Innsbruck, where the Eastern Alpine Conifer Chronology (EACC) has been established on the basis of calendar-dated tree-ring-width series (Nicolussi et al, 2009). We have utilized a large number of these sub- T. Arosio et al: Alpine Holocene tree-ring dataset Figure 1.…”
Section: Subfossil Wood Samples and Sampling Sites In The Alpsmentioning
confidence: 99%
“…Map of the location of the 29 sampling sites (© Google Maps 2020): they are situated in the Swiss, the Austrian, and the Italian Alps. Information on each site is given in Table 1. fossil wood samples that cover nearly the whole Holocene (Nicolussi et al, 2009). They belong to the deciduous larch (Larix decidua Mill.)…”
Section: Subfossil Wood Samples and Sampling Sites In The Alpsmentioning
confidence: 99%
See 1 more Smart Citation